Evaluation of the MicroSEQ™ Salmonella spp. Detection Kit with the PrepSEQ™ Rapid Spin Sample Preparation Kit for Detection of Salmonella spp. in Dry Pet Food. (27th November 2019) - Cloke, Jonathan; Flannery, Jonathan; Bastin, Benjamin; Bird, Patrick; Crowley, Erin Sutphin; Benzinger, M Joseph; Agin, James R; Goins, David; Chen, Yi
Abstract: A method modification validation study was conducted to validate the Applied Biosystems MicroSEQ™ Salmonella spp. Detection Kit for the detection of Salmonella spp. in 375 g samples of dried pet food. The MicroSEQ assay protocol, using the Applied Biosystems PrepSEQ™ Rapid Spin DNA Sample Preparation Kit, was compared to the reference method detailed in the U.S Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM; Chapter 5, Salmonella ) for detection of Salmonella spp. For each method, 20 replicates were analyzed at a low contamination level of 0.2–2 CFU/test portion, five replicates were analyzed at a high level of contamination of 2–5 CFU/test portion, and five control replicates were also analyzed at 0 CFU/test portion (uninoculated). Statistical analysis was conducted using the Probability of Detection statistical test to determine the ability of the MicroSEQ Salmonella spp. Detection Kit to detect Salmonella from 375 g samples of dried pet food in comparison to the FDA-BAM reference method. The results demonstrated that the MicroSEQ Salmonella spp. Detection Kit was able to accurately detect Salmonella spp. present in dry pet food after an enrichment time of 20 h.